Tingkat Depresi Terhadap Kualitas Hidup Penderita Kanker Serviks - Marta Yuanisa; Cicilia Wahju Djajanti; Yhenti Djajanti (Jurnal Keperawatan Muhammadiyah, 2022)
Cervical cancer is a disease that improve depression affects for life quality. Based on the phenomena found at Yayasan Kanker Indonesia, most of the patients lose their life expectancy and feel disappointed with their conditions due to the cancer. The objective of the study is to identify the relationship between the depression levels and life quality of the patients with cervical cancer at Yayasan Kanker Indonesia. This study used correlation design by using time-series cross-sectional approach. There are 34 respondents consisting of patients with cervical cancer who meet the inclusion criteria. They are selected by using consecutive sampling technique in the period of March to May 2017. The instrument used is BDI-II (Beck Depression Inventory - II) to measure the depression levels and WHOQOL – BREF (World Health Organization Quality Of Life) to assess the life quality. The result of the study shows that 38% of the respondents suffer from moderate depression; 35% of the respondents experience severe depression; 15% of the respondents are with mild depression, and 12% of the respondents do not feel depressed at all. More than 50% (65%) of the respondents have moderate life quality. The result of Rank Spearman test shows that p = 0,000 (α = 0,05) where p ˂ α, which means that H1 is accepted with the correlation coefficient of 0,779. It implies that there is a strong, positive relationship between depression levels and life quality of patients with cervical cancer. Therefore, it is suggested that the board of the management of Yayasan Kanker Indonesia provided palliative treatment that focuses not only on the physical treatment, but also on the psychological treatment in order to improve the patients’ life quality.